"Química – nossa vida, nosso futuro” : análise discursivo-textual do Ano Internacional da Química na revista Ciência Hoje - Fukui, Ana (Universidade do Vale do Rio dos Sinos, 2017)
The present work investigated Popularization of Science under the view of the Text Linguistics (KOCH, 2009) along with contributions of the epistemology of science (BACHELARD, 1996). The main objective was to understand how scientific knowledge is constructed in popularization of science texts. For this, actions were defined as: a proposal of a communication model that identified and described tje particularities of the chosen corpus; The construction of a dialogue with an epistemological approach of the corpus that seek to understand how science is represented and a search for evidence of previous items in selected texts. The theoretical basis discussed the communication models existing in the consolidation of the concept of communication situation and the communication contract (CHARAUDEAU, 2014) for the Ciência Hoje journal in the media, according to Semiolinguistics. Then there was a reference (MONDADA, 2002) articulation with an epistemology of science to stipulate a negotiation of meanings between the reader and scientist to consider common sense, only then to construct scientific knowledge. The methodology used justified the choice of the editorial of the first release of the year, the selection criteria of the texts and the sections to be analyzed. With these instruments 8 introductions of an amount of 18 texts that compose the corpus were selected to be analysed. The results obtained showed that some items of the communication contract were modified to adequately describe the conditions of framework of the Ciência Hoje journal. From the analysis performed with instruments of the Linguistics of the Text it was possible to understand how the construction of an object of discourse (MARCUSCHI, 2011) in the scientific dissemination occurs, in which there is an approximation between the common language and the scientific language. Another result to be highlighted is the presence of a recurrent text plan in the selected introductions, which has the same argumentative structure, although the textual strategies chosen by the authors are quite different. The results also showed that scientists consider emotions, intuition, chance and other knowledge associated with science as an integral part of science.
Keywords: Ciência hoje; Situação de comunicação; Epistemologia da ciência; Referenciação e negociação; Linguística do texto; Communication situation; Epistemology of science; Referenciation and negociation; Text linguistics; ACCNPQ::Lingüística, Letras e Artes::Lingüística